The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1189/jlb.0113022
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advance: Actin CytoFRET, a novel FRET flow cytometry method for detection of actin dynamics in resting and activated T cell

Abstract: Actin cytoskeleton plays a critical role in regulating T cell motility and activation. However, the lack of a real-time quantitative method to analyze actin assembly has limited the progress toward understanding actin regulation. Here, we describe a novel approach to probe actin dynamics on living T cells using FRET combined with flow cytometry. We have first generated a Jurkat T cell line stably coexpressing EGFP and mOrange FPs fused to actin. The real-time variation of actin monomer assembly or disassembly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This modification revealed that neither antagonist nor agonist treatment altered PPARγ1 - N-CoR2 binding ( Figure 6C and Supplementary Figure 6 ). Importantly, flow cytometry-based FRET efficiencies have to be calculated from raw flow cytometric data 10-12.…”
Section: Discussionmentioning
confidence: 99%
“…This modification revealed that neither antagonist nor agonist treatment altered PPARγ1 - N-CoR2 binding ( Figure 6C and Supplementary Figure 6 ). Importantly, flow cytometry-based FRET efficiencies have to be calculated from raw flow cytometric data 10-12.…”
Section: Discussionmentioning
confidence: 99%
“…Two channel emission ratio measurement has been applied a lot both in microscopy [ 74 , 75 ] and flow cytometry [ 76 , 77 ] as sensors of protein–protein interactions. Basically, the practice is to illuminate the doubly (donor and acceptor) labeled sample with the donor excitation wavelength, then, collect the signals in both donor and FRET channels, i.e ., in the wavelength range corresponding to the emission peak of the donor and acceptor, respectively.…”
Section: Methods For Measuring Fretmentioning
confidence: 99%
“…Jurkat cells were cultured at 37 °C in 5% CO 2 in RPMI supplemented with 10% fetal bovine serum (FBS) (Hyclone), and DMEM, 10% fetal bovine serum, respectively). Control (CT) and Actin CytoFRET (ACT) reporter cell lines were generated as previously described (Larbret et al, 2013). Antibodies against β-actin (C4) were purchased from Santa Cruz Biotechnology, cofilin (D3F9), ERK2 (9108), profilin (C56B8), ubiquitin (P4D1), and phospho-ADF/cofilin (3312) were purchased from Cell Signaling Technology.…”
Section: Cells Culture Antibodies and Reagentsmentioning
confidence: 99%
“…Plasmid constructions, cloning, and DNA sequencing were carried out according to standard protocols. For single color (EGFP or mOrange) and EGFP or mOrange fused to actin, cloning strategies were described previously (Larbret et al, 2013).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
See 1 more Smart Citation